Cerebrovascular amyloid angiopathy in bioengineered vessels is reduced by high‐density lipoprotein particles enriched in apolipoprotein E: Development of new models and analysis methods/amyloid/Abeta. (7th December 2020) - Robert, Jerome; Button, Emily B.; Martin, Emma; McAlary, Luke; Gidden, Zoe; Gilmore, Megan; Boyce, Guilaine K.; Caffrey, Tara M.; Agbay, Andrew; Clark, Amanda; Silverman, Judith M; Cashman, Neil R.; et al.
Abstract: Background: Several lines of evidence suggest that high‐density lipoprotein (HDL) reduces Alzheimer's disease (AD) risk by decreasing vascular beta‐amyloid (Aβ) deposition and inflammation, however, the mechanisms by which HDL improve cerebrovascular functions relevant to AD remain poorly understood. Methods: Here we use a human bioengineered model of cerebral amyloid angiopathy (CAA) to define several mechanisms by which HDL reduces Aβ deposition within the vasculature and attenuates endothelial inflammation as measured by monocyte binding. Results: We demonstrate that HDL reduces vascular Aβ accumulation independently of its principal binding protein, scavenger receptor (SR)‐BI, in contrast to the SR‐BI‐dependent mechanism by which HDL prevents Aβ‐induced vascular inflammation. We describe multiple novel mechanisms by which HDL acts to reduce CAA, namely: i) altering Aβ binding to collagen‐I, ii) forming a complex with Aβ that maintains its solubility, iii) lowering collagen‐I protein levels produced by smooth‐muscle cells (SMC), and iv) attenuating Aβ uptake into SMC that associates with reduced low density lipoprotein related protein 1 (LRP1) levels. Furthermore, we show that HDL particles enriched in apolipoprotein (apo)E appear to be the major drivers of these effects, providing new insights into the peripheral role of apoE in AD, in particular, the fraction of HDL that contains apoE. Conclusion: The findings in this study identify new mechanisms by which circulating HDL, particularly HDL particles enriched in apoE, may provide vascular resilience to Aβ and shed new light on a potential role of peripherally‐acting apoE in AD.